2012
DOI: 10.1126/science.1219643
|View full text |Cite
|
Sign up to set email alerts
|

Direction-Specific Interactions Control Crystal Growth by Oriented Attachment

Abstract: The oriented attachment of molecular clusters and nanoparticles in solution is now recognized as an important mechanism of crystal growth in many materials, yet the alignment process and attachment mechanism have not been established. We performed high-resolution transmission electron microscopy using a fluid cell to directly observe oriented attachment of iron oxyhydroxide nanoparticles. The particles undergo continuous rotation and interaction until they find a perfect lattice match. A sudden jump to contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

59
1,066
5
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,019 publications
(1,132 citation statements)
references
References 28 publications
59
1,066
5
2
Order By: Relevance
“…Each region with similar orientation appears contiguous ( Supplementary Fig. S6), which is consistent with growth by oriented attachment 3,6 .…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Each region with similar orientation appears contiguous ( Supplementary Fig. S6), which is consistent with growth by oriented attachment 3,6 .…”
supporting
confidence: 67%
“…These nanoparticle-based materials provide a unique challenge in assessing structure-property relationships because of the disordered arrangement of nanocrystals that results when nanoparticles collide and aggregate [2][3][4][5][6] . The morphological evolution that follows aggregation further obscures the influence of particle size, shape, and interfacial characteristics in defining the physical properties of these materials 7,8 .…”
Section: Use Policymentioning
confidence: 99%
“…In contrast, when the size of smaller nanoparticle is close to or larger than the critical size d c , the coalescence becomes more dependent on the orientation (Figure 3m–x). Compared to the rapid atomic migration and rearrangement for the small particles (particle size smaller than critical size d c ), the slow atomic migration and rearrangement rates are observed in the big nanocrystals, resulting in the formation of relatively stable grain boundary after contact of the two particles 17, 39, 40…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Particle coalescence has been observed for haematite, iron oxyhydroxide, platinum-iron alloy, platinum, silver, and gold, allowing for assessment of coalescence features such as preferred particle orientations and kinetics. [12][13][14][24][25][26] When performing these experiments, care must be taken to avoid electron beam artifacts, such as specimen charging/reduction, flow effects, and bubbles, that can influence specimen behavior. 18,21,22,27,28 However, recent experimental observations have shown that these effects can be quantified, controlled and mitigated using calibrated electron doses.…”
mentioning
confidence: 99%